Analisis Rendahnya Produktivitas CV. Dua Putra Srikandi dalam Meningkatkan Pendapatan Karyawan Di Padang Kadok Kecamatan Kinali (Studi Kasus CV. Dua Putra Srikandi di Padang Kadok) : - Yusita Yusita; Fawza Rahmat; Maisarah Leli (STAI YAPTIP, 2024)
ABSTRACT This study aims to analyze the factors affecting low productivity at CV. Dua Putra Srikandi, an oil palm processing company located in Padang Kadok, Kinali District. The decrease in productivity is influenced by several constraints, including limited production facilities, lack of employee training and motivation, and inadequate working conditions. The research uses a descriptive qualitative approach with data collection through observation, structured and semi-structured interviews, and document analysis. The results show that the main factors contributing to low productivity are the limited skills of employees, insufficient production facilities, and low work motivation. The impacts include financial losses, product quality decline, and loss of competitiveness. This study recommends strategic steps such as increasing production capacity, routine skills training, and maintaining facilities and equipment. It is expected that with the implementation of these recommendations, CV. Dua Putra Srikandi can improve operational efficiency and productivity, ultimately positively impacting employee welfare and the company’s competitiveness. Keywords: Productivity, CV. Dua Putra Srikandi, Employee Skills, Production Facilities, Work Motivation, Product Quality, Competitiveness.